Composition And Structure Of Undergrowth Habitats Of Flora Rafflesia arnoldii R.Br. In The Forests Of Bukik Pinang Mancuang, Kamang Mudiak, Agam - Rizka Sefmaliza; Chairul Chairul (Jurnal Biologi Universitas Andalas, 2022)
Vegetation analysis is a way of studying the composition of species and the structure of the vegetation. The objective research about understorey vegetation analysis in the flora habitat of Rafflesia arnoldii in Bukit Pinang Mancuang Forest, Kamang Mudiak, Agam was to determine the composition and structure in the flora habitat of Rafflesia arnoldii in Bukit Pinang Mancuang Forest, Kamang Mudiak, Agam. Vegetation analysis was carried out by using the quadratic plot method with a size of 2 x 2 m. There were 6 plots have been made and species identification was carried out at the Andalas University Herbarium. According to the observation result, there are 32 species discovered consisting of 601 individuals with 19 families. The dominant families are Rubiaceae (34.61%) and Utricaceae (32.61%). The importance value index of Coffea canephora was obtained (51.28%). The plant diversity index in this area was classified as moderate (H'=2.58). Based on the analysis conveyed, it can be concluded that the Rubiaceae and Urticaceae families are adequate forest and life support for Rafflesia arnoldii habitat. It is recommended that the local government designated the forest as a conservation area in order to preserve the existence of Rafflesia arnoldii and its habitat.